Protecting the Vulnerable: Social Safety Nets and Household Consumption in Yogyakarta City - Nuryadin Didi; Hapsoro Darpito Surpiko; Umaroh Rodhiah; Astyka Rahmanda Gita (SHS Web of Conferences)
This study examines the impact of social safety net programs on household welfare proxied by their consumption of food and non-food commodities in Yogyakarta City. The research aims to understand how different safety net initiatives, such as conditional cash transfer (Program Keluarga Harapan & Kartu Keluarga Sejahtera), food subsidies (Bantuan Pangan), and Non-cash of food (Bantuan Pangan Non-Tunai). A methodology of descriptive statistics and t-tests was applied to assess the impact of social safety net programs. The findings reveal significant variations in consumption responses, with lower-income households showing a pronounced dependence on these programs. It was found that the impact is more on households’ food expenditure. This highlights the program’s success and the need for its continuation or expansion to reduce poverty further and enhance the well-being of vulnerable households.